Pengaruh Pelayanan Terhadap Kepuasan Anggota Yang Menabung di KSP CU Keling Kumang BO Siantan Pontianak - Darius Damestuteles (Pusat Penelitian dan Pengabdian kepada Masyarakat, 2022)
The quality of service certainly affects the satisfaction of members who save at KSP CU Keling Kumang BO Siantan Pontianak. After being analyzed and researched, the results of the study show that there is a close relationship and dependence between service quality and member satisfaction. The higher the quality of service provided by the employees of KSP CU Keling Kumang BO Siantan Pontianak, the better for members who save. The compatibility between expectations and the reality expected by members of KSP CU Keling Kumang of course must be maintained and services must continue to improve, so that the expectations of members are the same as the reality they receive or receive. This research examines three variables regarding service quality, which consist of Technical Quality (X1), Functional Quality (X2), Corporate Image (X3). Of the three variables, it is very influential and has a positive and significant influence on the satisfaction of members who save at KSP CU Keling Kumang BO Siantan Pontianak.